AIOps: Real-World Challenges and Research Innovations - Dang, Yingnong; 林庆维, Qingwei Lin; Huang, Peng (ICSE'19, Technical Briefings, 2019)
AIOps is about empowering software and service engineers (e.g., developers, program managers, support engineers, site reliability engineers) to efficiently and effectively build and operate online services and applications at scale with artificial intelligence (AI) and machine learning (ML) techniques. AIOps can help improve service quality and customer satisfaction, boost engineering productivity, and reduce operational cost. In this technical briefing, we first summarize the real-world challenges in building AIOps solutions based on our practice and experience in Microsoft. We then propose a roadmap of AIOps related research directions, and share a few successful AIOps solutions we have built for Microsoft service products.